Anemia as a Risk Factor for Acute Lower Respiratory Tract Infection in Children Below Five Years of Age - Shakya, Henish; Singh, Saurav; Lakhey, Ashish (Nepalese Medical Journal, 2018)
Introduction: Lower respiratory tract infection is a major cause of death in children in a developing country and anemia is found to be one of the commonest associated cofactors. This study was aimed to determine association of anemia in children with lower respiratory tract infections. Materials and Methods: The retrospective study was done over a one-year period for children under 5 years of age, admitted in Pediatric Ward of a tertiary Hospital in Lalitpur. The study included 100 diagnosed cases of lower respiratory tract infections as per WHO criteria and 100 age and sex matched patients who did not have respiratory complaints as controls, excluding prematurity, chronic diseases, malnutrition and severe systemic illness. Appropriate clinical history, examination routine investigations like hemoglobin, peripheral smear, and Chest X-ray were included. Results: The age distribution maximum children were in the age group of 3 months to 23 months with significant association with prevalence of both pneumonia (p value 0.005) and anemia (p value 0.002). Anemia was found to be a significant risk factor for LRTI (p value < 0.001) with odds ratio of 2.68 and 95% CI (1.51 – 4.75). Conclusions: Anemia was significantly found to be associated with lower respiratory tract infections and these children were found to be 2.68 times more susceptible to lower respiratory tract infections. Early diagnosis and prevention of anemia is thus important to reduce the incidence of lower respiratory tract infections in children. Nepalese Medical Journal. vol.1, No. 1, 2018, page: 5-8